Physicochemical and Nutritional Properties of Doi Fortified with Psyllium Husk and Basil Seed (Bangladesh Journal of Animal Science, 2022)
This work was carried out to evaluate the physical, chemical and microbiological qualities of doi fortified with psyllium husk (Plantago ovate) and basil seed (Ocimum basilicum). Seven different types of doi - A (control), B (with 0.4% psyllium husk), C (with 0.8% psyllium husk), D (with 1.2% psyllium husk), E (with 0.7% basil seed), F (with 1.4% basil seed) and G (with 2% basil seed) were prepared. The highest total sensory score (86.67) was obtained in A type doi which differ non-significantly with B (81.67) and E (78.67) type doi. Addition of higher level of fiber lowered the overall physical score but with a higher total solids content of the doi. The higher fat and protein content were found in the doi with basil seeds which ranged from 4.88-4.97% and 3.90-4.21%, respectively. The addition of psyllium husk and basil seed significantly increase the crude fiber content of the doi and the highest value (0.41-0.48%) being recorded in D and G type doi. This fortification also helps to reduce the syneresis of the doi both at room and refrigeration temperature without affecting the total viable count. Therefore, doi can be fortified with dietary fiber without affecting much of its quality attributes.Bang. J. Anim. Sci. 2021. 50 (2): 99-106